Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-146
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Experimental With Computational Results in an Annular Turbine Cascade With Emphasis on Losses

Abstract: Recent discussions in the industrial CFD community have identified a need for guidelines covering the accurate and efficient computation of a range of flow field classes. This paper addresses some of these issues for a standard turbomachinery test case, by investigating the flow through on annular blade row of a generic turbine profile, operating at an exit Mach number of 0.5. The joint experimental and CFD works have focused upon identifying and quantifying the loss sources and loss development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The values for the inlet turbulence intensity and inlet eddy length scale were investigated by performing several simulations combining difference values. A similar study was performed Casciaro et al [10] using the same software. In the present study it was found that Tu=5% and L ε =0.05m presented the best agreement with the experimental data.…”
Section: Boundary Conditionsmentioning
confidence: 75%
See 1 more Smart Citation
“…The values for the inlet turbulence intensity and inlet eddy length scale were investigated by performing several simulations combining difference values. A similar study was performed Casciaro et al [10] using the same software. In the present study it was found that Tu=5% and L ε =0.05m presented the best agreement with the experimental data.…”
Section: Boundary Conditionsmentioning
confidence: 75%
“…The three-dimensional, steady-state, Reynolds-averaged, compressible Navier-Stokes equations were solved with the CFX-TASCflow 2.10.0 computational code. Several numerical analyses of the flow field inside turbomachinery were performed by using this code, as described by Labrecque et al [9], Casciaro et al [10], von Hoyningen-Huene and Hermeler [11], Casciaro et al [12] and Favaretto [13].…”
Section: Computational Codementioning
confidence: 99%
“…For the no-clearance case (Fig. 6a), the typical features associated with the secondary flow field are seen [13]. Because of the decision to use a constant contour step of 0.5 for all four plots, some of the fine detail of the measured flow field for this case is lost in this figure.…”
Section: Presentation Of the Principal Resultsmentioning
confidence: 93%
“…For a discussion of the use of the exit static pressure distribution as a boundary condition see Section 3.3. An in-depth discussion of the issues relating to the validation of the code can be found in references [13] and [14]. The aim of this paper is to generate an experimental data set for CFD validation data, and it is outside the scope of the paper to discuss all the issues raised by the numerical simulation.…”
Section: Numerical Methodologymentioning
confidence: 99%
See 1 more Smart Citation